2013
DOI: 10.1136/sextrans-2012-050980
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine acceptability among men: a systematic review and meta-analysis

Abstract: ObjectiveTo understand rates of human papillomavirus (HPV) vaccine acceptability and factors correlated with HPV vaccine acceptability.DesignMeta-analyses of cross-sectional studies.Data sourcesWe used a comprehensive search strategy across multiple electronic databases with no date or language restrictions to locate studies that examined rates and/or correlates of HPV vaccine acceptability. Search keywords included vaccine, acceptability and all terms for HPV.Review methodsWe calculated mean HPV vaccine accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
118
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 52 publications
6
118
2
Order By: Relevance
“…20,21,22 This may be due to poor knowledge relating to HPV infection, HPV associated disease and HPV vaccine in MSM in Ireland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21,22 This may be due to poor knowledge relating to HPV infection, HPV associated disease and HPV vaccine in MSM in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…While this was not examined in our study it should be considered when education programs are being developed. 20 Perception that HPV vaccine will protect against genital warts, penile and anal cancers were associated with HPV vaccine acceptability on univariate analysis (Table 5) As factors reported as associated with HPV vaccine acceptability are based on the scenario of no cost vaccine, perception that market cost of the vaccine is high may attribute a value to the vaccine and represent an incentive to avail of no cost vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Our figure on the acceptance of HPV vaccine among MSM was lower than that in a recently published systematic review on data from various countries (36-74%). 36 This may be because of the lack of knowledge of HPV vaccine and the perception that HPV vaccine was a female vaccine and irrelevant to men. 36 Younger MSM may be more accepting of HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…36 This may be because of the lack of knowledge of HPV vaccine and the perception that HPV vaccine was a female vaccine and irrelevant to men. 36 Younger MSM may be more accepting of HPV vaccination. An Australian study of 200 MSM aged 16 to 20 found that of these young men 86% would be willing to take the vaccine if it was free of charge to MSM, albeit only 30% would purchase it.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 4065 males aged 16-26, the quadrivalent HPV vaccine was shown to be effective in preventing genital warts, penile cancer and anal cancer. 1,9 In addition, a meta-analysis of 29 studies (8360 men) that reported on HPV vaccine acceptability found a moderate level of acceptability in men, 10 indicating that men would have the HPV vaccine if it was offered.…”
Section: Effective Vaccinesmentioning
confidence: 99%